KESANTUNAN BERBAHASA SISWA PADA PROSES PEMBELAJARAN BAHASA INDONESIA DI KELAS VIII SMP NEGERI 1 BENGKULU UTARA - Devi Maliza (Universitas Bengkulu, 2018)
The purpose of this study to describes about language politeness, violation of language politeness, language politeness strategy and the marker of language politeness of class VIII students’ at SMP Negeri 01 Bengkulu Utara. This research uses qualitative method. The sources of research data obtained based on the students’ conversation during the learning process, while the research data is recording students’ conversations in the classroom. Data analysis techniques through some stages; (1) Researchers make the recording during the learning process. Conversations recorded in the classroom, there is no limited to specific learning materials, but each learning process in the class room. (2) The researcher copy the recorded conversations into written form. (3) Transcribed data was grouped based on conversations between students-students and students-teachers. (4) The data analysis using the principles of politeness developed by Leech, namely maxim of wisdom, maxim of generosity, maxim of praise, maxim of consent, maxim of generosity and maxim of sympathy. (5) The research conclusions are based on data that has been processed or analyzed. Based on the results of the research (1) The fulfillment of SMPN 01 Bengkulu Utara's language companionship based on Leech's theory found six maxims of politeness in the learning process: maxim of wisdom, maxim of generosity, maxim of praise, maxim of humility, maxim of consent and maxim of sympathy. (2) Violations of students' language politeness are found in maxim of praise, while the other five maxims are not found in violation of politeness. (3) Positive language politeness strategy consists of: giving promise and giving approval. Negative politeness strategies consist of: Demonstrating pessimism, minimizing coercion, asking for forgiveness and impersonal use, and (4) The language modesty markers in the findings of this study are: linguistic markers of politeness and committers.Keywords:politeness, strategy, bookmark, student